In praise of promoting prisms of praise - Jacobs, George M; Hall, Stephen J (Journal of Modern Languages, 2020)
Advice for teachers often includes advice on the quality and quantity of the praise they give students. The present article reviews and perhaps adds to that advice, as well as cautioning that the influence of culture needs to be borne in mind when praise is considered. The two theories discussed in the introductory part of this article, Behaviorism and Social Constructionism, provide different but not necessarily incompatible advice on praise. The article’s twelve specific suggestions on praise may be a useful review or new ideas. Included among those suggestions are ideas for involving people other than teachers in praising students, to praise not just the result but also the process used towards that result and those who helped in the process, and in giving praise, to highlight the class’s long-term goals. Certainly, the suggestions are relevant not only for teachers but also for other stakeholders in Education and beyond.